2016
DOI: 10.1136/bcr-2016-216641
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab: a novel treatment for ipilimumab-induced colitis

Abstract: Use of the immune checkpoint inhibitors, ipilimumab and nivolumab, has revolutionised treatment in patients with metastatic melanoma. However, these drugs can cause an autoimmune enterocolitis, with diarrhoea as the presenting symptom. This is conventionally managed by prompt institution of corticosteroid therapy if moderate diarrhoea (3-6 times/day; grade 2) is present for >5 days or if diarrhoea is severe (>6 times/day; grade 3). We report a case of steroid-dependent ipilimumab-induced colitis successfully t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…These results corroborate a recent report on a single patient who had developed colitis secondary to ipilimumab therapy and was successfully treated with vedolizumab [29]. The patients selected for vedolizumab therapy in our retrospective study were either steroid-dependent and/or partially steroid refractory.…”
Section: Discussionsupporting
confidence: 91%
“…These results corroborate a recent report on a single patient who had developed colitis secondary to ipilimumab therapy and was successfully treated with vedolizumab [29]. The patients selected for vedolizumab therapy in our retrospective study were either steroid-dependent and/or partially steroid refractory.…”
Section: Discussionsupporting
confidence: 91%
“…[149][150][151] Case series and reports have also documented successful treatment of ICI-mediated, steroid-dependent, or steroid-refractory enterocolitis with vedolizumab. 76,152 Vedolizumab may be effective in the setting of infliximabresistant inflammation of the small intestine and colon. 77…”
Section: Gi Toxicitymentioning
confidence: 99%
“…Vedolizumab is a humanized monoclonal IgG1 antibody against α4β7 integrin, approved for treatment of IBD. Some case reports suggest that vedolizumab may be an effective drug in steroid-refractory or steroid-dependent patients [24, 25]. A recent study with seven patients with mild to moderate, steroid-dependent or steroid-refractory ipilimumab-induced enterocolitis has revealed that six out of seven patients treated with vedolizumab achieve remission and no adverse events were reported [26].…”
Section: Managementmentioning
confidence: 99%